GROUNDING PEDAGOGICAL CONDITIONS OF WOULD-BE TOURISM MANAGERS’ SELF-IMPROVEMENT IN EXTRACURRICULAR ACTIVITIES - Zahnybida, R. (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
Reforming of the modern educational system requires a fundamentally new approach to training managers of tourism for their professional career. Active search of ways to improve the educational technologies of training tourism managers focused on the formation of professional competence, development of creative and potential abilities, security of effective conditions for student’s self-improvement in extracurricular activities are made today. The purpose of the article is the grounding of pedagogical conditions of would-be tourism managers’ self-improvement in extracurricular activities. The article analyzes the features of professional training of would-be tourism managers. Pedagogical conditions of would-be tourism managers’ self-improvement have been grounded. It has been argued that the successful effectiveness of the formation process of the need for professional self-improvement of future tourism managers depends on the compliance of the following pedagogical conditions: would-be tourism managers’ preparedness formation for professional self-improvement; phasing the process of would-be tourism managers’ professional self-improvement; motivation to participate in various forms of extracurricular activities. It has been proved that the basic rules which should be followed in the process of organizing students’ extracurricular activities in the university must be: diversifying forms of extracurricular activities; compliance with the clear content of tasks for students in extracurricular activities; formation of interest in future professional career; stimulation of the need for self-development, self-training and self-education. Prospects for further research are in the development of appropriate scientific and methodological complex materials, in particular – guidelines for teachers concerning the organization of extracurricular activities, improvement of students’ individual work.